Floristic inventory of the Natural Protected Area Parque Nacional El Potosí, San Luis Potosí, Mexico - de Nova, Arturo; Enríquez-Salaices-Valdez, Estrella; Castillo Lara, Pedro; Cilia-López, Virginia Gabriela; Yañez-Espinosa, Laura; Gudiño-Cano, Ana Karem; Vázquez-Mendoza, Sadoth (Instituto de Ecología, A.C., 2023)
Background and Aims: Mexico presents a great diversity of vascular flora given its geographical, orographic and climatic conformation. However, many sites have incomplete or non-existent floristic inventories. This is the case of El Potosí National Park Protected Natural Area, which despite having been established in 1936, lacks an updated inventory of its vascular flora. The objective of this work was to obtain such inventory, as a reference of temperate forests in the Sierra Madre Oriental. Endemic species to Mexico and San Luis Potosí and adjacent regions are highlighted, as well as those in some category of risk. Methods: Botanical collections were made in a gradient from 1800 to 2390 m a.s.l., between June 2017 and September 2018. Data about the habitat, phenology and growth form were recorded. The taxonomic biodiversity index in the studied area was compared with other temperate forest regions in the state of San Luis Potosí. Key results: A total of 354 species of vascular plants are registered, of 228 genera in 83 families. The families with the highest species richness are Asteraceae, Fabaceae, Fagaceae, Lamiaceae and Polypodiaceae. The taxonomic biodiversity in the area is similar to those reported for other regions with temperate forests in San Luis Potosí. The area includes 99 endemic species to Mexico, and six exclusive of San Luis Potosí and adjacent areas. In addition, six species are listed in some risk category according to NOM-059-SEMARNAT-2010, 16 in the CITES appendices and 14 in some risk category of the Red List of the IUCN. Conclusions: The species richness, its endemism and diversity, as well as the presence of threatened species, highlights the importance of the Parque Nacional El Potosí as priority region for the conservation of the temperate forest in the Sierra Madre Oriental.